1958
DOI: 10.1017/s0021859600029841
|View full text |Cite
|
Sign up to set email alerts
|

The act of rumination

Abstract: 1. A detailed analysis was made of the rumination behaviour of one caged sheep on four combinations of diet, ranging from 100% hay to 100% concentrate meal.2. When hay was fed there was no relationship between the quantity of it ingested and the amount of rumination, which averaged 8 hr. daily. When concentrates were fed alone rumination time fell to 2½ hr. per day and much of this was ‘pseudorumination’.3. Evidence is produced to show that the number of chews and not the time chewing is the accurate way of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1
2

Year Published

1961
1961
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
6
20
1
2
Order By: Relevance
“…chewing frequency) changed without total rumination time changing. This factor was discussed by Gordon (1958) who observed (Gordon, 1965) in sheep a closer relationship between time spent actually chewing during rumination and feed intake than between intake and total rumination time. Further work should compare in sheep and cattle chewing frequency during rumination and the actual time spent chewing during rumination.…”
Section: Eating and Ruminating Behaviourmentioning
confidence: 99%
“…chewing frequency) changed without total rumination time changing. This factor was discussed by Gordon (1958) who observed (Gordon, 1965) in sheep a closer relationship between time spent actually chewing during rumination and feed intake than between intake and total rumination time. Further work should compare in sheep and cattle chewing frequency during rumination and the actual time spent chewing during rumination.…”
Section: Eating and Ruminating Behaviourmentioning
confidence: 99%
“…Hafez (1952) reported that lactation seemed to defer post parturient oestrus. The percentage of both Merino and Dorset Horn ewes which were lactating when post parturient oestrus occurred was considerably greater and post parturient oestrus occurred sooner after parturition than in the studies recorded by Gordon (1958) involving other breeds and crosses. More Merino than Dorset Horn ewes were lactating when post parturient oestrus occurred after both a winter and summer lambing.…”
Section: Discussionmentioning
confidence: 58%
“…As diferenças entre os estádios de lactação, quanto ao padrão de dispersão da atividade de rumi- A importância do componente de ritmo 1 em relação aos outros componentes de ritmo, para descrever o padrão de distribuição circadiano da ruminação, no início e no final da lactação, está de acordo com observações anteriores sobre consistência da ruminação durante o período noturno (Gordon, 1958;Gordon & Mc Allister, 1970;Deswysen et al, 1989Deswysen et al, , 1993. A importância dos componentes de ritmo 2 e 3 foi associada, respectivamente, à atividade de ruminação no início da tarde, também descrita por Pearce (1965) e Deswysen et al (1989Deswysen et al ( , 1993) e à existência de um pequeno pico da atividade entre 7 e 8h.…”
Section: Horas Do Dia Hours Of the Dayunclassified